Efficacy of ethyl formate as a disinfestation treatment for codling moth (Cydia pomonella) in apples - Jamieson, L.E.; Page-Weir, N.E.M.; Griffin, M.J.; Redpath, S.P.; Chhagan, A.; Connolly, P.G. (New Zealand Plant Protection, 2016)
Codling moth (CM Cydia pomonella) is a pest of quarantine concern on apple exports to Asian markets Apples exported to Japan must be fumigated with methyl bromide (MB) and then cold stored Ethyl formate (EF) as an alternative to MB is effective against a range of pests This project investigated the effectiveness of EF to control an internal pest such as CM by determining the responses of key insect stages without fruit and inside apples Trials without fruit in a 2 h fumigation showed that latestage CM eggs and third instar CM larvae were the most tolerant life stages requiring a mean concentration of 134194 EF to achieve 99 mortality but 100 mortality of 4th/5th instar CM larvae Trials with CM in fruit in a 2 h fumigation showed that 113 EF resulted in 534 mortality of 4th/5th CM larvae inside apples Increasing the mean concentration to 24 EF increased the mortality of 4th/5th larvae inside apples to 852